2015
DOI: 10.15835/nbha4319773
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization and Relationships of Turkish Local Eggplant Heirlooms

Abstract: A total of 38 eggplant genotypes, of which 32 were heirloom accessions collected from different regions of Burdur province five were different local genotypes from other provinces, and one was a cultivar, were used as reference in this study. The phylogenetic relationships among these heirlooms were evaluated using 40 morphologic descriptors and five randomly amplified polymorphic RAPD markers. The horizontal dendrograms were created by using UPGMA with both morphologic and molecular data. Burdur heirloom acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…As occurred for morphological traits, the wide variation observed for mineral composition agrees with other works in which a significant number of eggplant accessions, commercial varieties, and hybrids were evaluated [65]. In the present study, significant differences were found only for Mg among island and mainland accessions, while non-significant differences were observed for Fe, Mn, Zn, Cu, and K. Raigón et al [39] and Arivalagan et al [38][39][40] studied the mineral composition and the nutritional value of eggplant landraces and germplasm accessions from different regions in order to identify mineral-rich germplasm for breeding purposes.…”
Section: Mineral Compositionsupporting
confidence: 88%
See 3 more Smart Citations
“…As occurred for morphological traits, the wide variation observed for mineral composition agrees with other works in which a significant number of eggplant accessions, commercial varieties, and hybrids were evaluated [65]. In the present study, significant differences were found only for Mg among island and mainland accessions, while non-significant differences were observed for Fe, Mn, Zn, Cu, and K. Raigón et al [39] and Arivalagan et al [38][39][40] studied the mineral composition and the nutritional value of eggplant landraces and germplasm accessions from different regions in order to identify mineral-rich germplasm for breeding purposes.…”
Section: Mineral Compositionsupporting
confidence: 88%
“…These same types of morphological traits were also the most variable ones when eggplant accessions collected from Greece, Spain, Turkey, and remote centers of diversity were studied [23,34,35,65,66]. Consistent with previous works, the amount of diversity is comparable to that observed in the characterization of germplasm from other geographical areas of the Mediterranean region [34,35,[64][65][66], providing further evidence that several areas of the Mediterranean region can be considered as secondary centers of diversity for eggplant [35,64].…”
Section: Morphological Diversitysupporting
confidence: 82%
See 2 more Smart Citations
“…Several characterization studies in eggplant with standardized morphological and agronomic descriptors developed by the European Eggplant Genetic Resources Network (EGGNET; van der Weerden and Barendse, 2007 ) and the International Board for Plant Genetic Resources (IBPGR, 1990 ) have revealed that are suited for providing a useful morphological and agronomic characterization for eggplant breeders (Prohens et al, 2005 ; Muñoz-Falcón et al, 2009 ; Boyaci et al, 2015 ). EGGNET and IBPGR descriptors have been successfully used for evaluating segregating generations of interspecific crosses between eggplant and related species (Prohens et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%